STRATEGI KOMUNIKASI PEMASARAN PP DARUSSALAM BLOKAGUNG DALAMMEMBANGUN CITRA INSTITUSI(STUDI KASUS PENGGUNAANMEDIASOSIAL) - Muhammad Ali Musafaat (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Digital technology development encourages Islamic educational institutions like Islamic boarding schools to adapt in maintaining their existence and building a positive image. This study aims to analyze the marketing communication strategy of Darussalam Blokagung Islamic Boarding School in building an institutional image through social media and determine its contribution to attracting prospective students. Theresearchusesaqualitativeapproachwithacasestudymethod. Datacollec tion techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and drawing conclu sions. The results showed that the marketing communication strategy was integrated through five pillars of Integrated Marketing Communication (IMC). These pillars are digital advertising, content based public relations, direct marketing through messaging services, interactive marketing, and dig ital word of mouth optimization. The implementation of this strategy successfully formed a solid institutional image based on Frank Jefkins’ four image elements. These elements are a personality that combines salaf tradition and modernity, reputation through publication of achievements, Is lamic values, and a consistent corporate identity. This strategy proved effective in increasing public trust and the attractiveness of new prospective students in the digital era.